2016
DOI: 10.1186/s12870-016-0779-3
|View full text |Cite|
|
Sign up to set email alerts
|

SNP-based analysis of genetic diversity reveals important alleles associated with seed size in rice

Abstract: BackgroundSingle-nucleotide polymorphisms (SNPs) have become the genetic markers of choice in various genetic, ecological, and evolutionary studies. Genotyping-by-sequencing (GBS) is a next-generation-sequencing based method that takes advantage of reduced representation to enable high-throughput genotyping using a large number of SNP markers.ResultsIn the present study, the distribution of non-redundant SNPs in the parents of 12 rice recombination line populations was evaluated through GBS. A total of 45 Giga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…Detection of genetic diversity using molecular markers of ISSR has been carried out in several previous studies (Wang et al, 2012;Patel et al, 2015;Taheri et al, 2013;Wang et al, 2017). Single nucleotide polymorphisms are the genetic markers of choice in various genetic, ecological and evolutionary studies (Tang et al 2016). In this study, the level of polymorphism of pisang ambon DNA bands obtained by gamma irradiation is quite high, namely, at 90%.…”
Section: Analysis Of Issr Molecular Markersmentioning
confidence: 77%
“…Detection of genetic diversity using molecular markers of ISSR has been carried out in several previous studies (Wang et al, 2012;Patel et al, 2015;Taheri et al, 2013;Wang et al, 2017). Single nucleotide polymorphisms are the genetic markers of choice in various genetic, ecological and evolutionary studies (Tang et al 2016). In this study, the level of polymorphism of pisang ambon DNA bands obtained by gamma irradiation is quite high, namely, at 90%.…”
Section: Analysis Of Issr Molecular Markersmentioning
confidence: 77%
“…Defects in BR biosynthesis produce smaller seeds, but it is still uncertain how BRs promote seed growth (Hong et al, 2002(Hong et al, , 2003. It is noteworthy that several CYP family members are involved in seed size control, including the Arabidopsis CYP78A5, CYP78A6, and CYP78A9 (Adamski et al, 2009;Fang et al, 2012), and soybean CYP78A72 and CYP78A10 (Wang et al, 2015b;Zhao et al, 2016), which all act as positive regulators of grain size, whereas the rice CYP78A13 and CYP704A3 (Xu et al, 2015a;Tang et al, 2016) act as negative regulators. NAC genes have been implicated in the control of seed size via the control of various stages of seed development (Agarwal et al, 2011).…”
Section: Potential Candidate Genes Controlling Grain Size Were Identimentioning
confidence: 99%
“…Singlenucleotide polymorphisms have become the genetic markers of choice in various genetic, ecological, and evolutionary studies (Tang et al, 2016). In the present study, SSR markers were used to detect genetic variation among 24 rice genotypes; in a separate analysis (data not shown here), morphological features were combined with the SSR results, and it was found that there was general agreement between the two sets of data with respect to pair-wise genetic distances among the rice cvs.…”
Section: Discussionmentioning
confidence: 77%